A RANDOMIZED CONTROLLED TRIAL ON THE ISLAMIC-BASED PROGRAM USING FAMILY APPROACHES IN PREVENTING ADOLESCENTS’ SMOKING BEHAVIOR IN INDONESIA: A STUDY PROTOCOL - Fithria Fithria; Muhammad Adlim; Syarifah Rauzatul Jannah; Teuku Tahlil (Belitung Nursing Journal, 2020)
Background: Smoking is a significant problem especially among Indonesian adolescents. A number of smoking prevention programs have been developed and implemented, but most of them do not work significantly for the Indonesian adolescents who are mostly Muslim. Objective: The aim of this article is to outline a study protocol for measuring the effects of Islamic-based program using family approaches on the prevention of adolescents’ smoking behavior. Methods: The study will use a cluster randomized controlled trial conducted in three junior high schools, in Aceh Province, Indonesia. A total of 150 students will be involved in this study, where each school will be represented by 50 students. Each school group will be given the respective treatments. The first group will receive health-based intervention program, the second group will receive Islamic-based intervention program, and the last group will act as a control group receiving no intervention. The outcomes include the knowledge about smoking, attitudes toward smoking, smoking intention and smoking behavior of the adolescents. All outcomes will be measured using validated questionnaires. Discussion: If the Islamic-based intervention using family approach is effective, then this approach could be implemented not only in Indonesia but also in other countries with the same social characteristics. Trial registration: Australian New Zealand Clinical Trial Registry, ACTRN 12620000465954